Association of variabilities in body mass index and metabolic parameters with post-kidney transplantation renal outcomes - Hyo Jeong Kim; Kyung Won Kim; Cheol Woong Jung; Jun Young Lee; Ji Yoon Choi; Beom Seok Kim; Myoung Soo Kim; Jaeseok Yang (Scientific Reports)
Abstract Metabolic syndrome is a significant risk factor for poor graft outcomes in kidney transplant (KT) patients. However, the effects of variability in metabolic parameters on graft outcomes in KT patients have not been completely elucidated. A total of 852 KT patients were included from the Korean Organ Transplantation Registry. The study exposure was variability in body mass index (BMI) or other metabolic parameters measured at 6 months, 1 year, and 2 years after KT. Patients were classified into tertiles according to the degree of variability. The primary outcome was a composite of adverse kidney outcomes, such as death-censored graft loss or ≥ 30% decline in estimated glomerular filtration rate. The adverse kidney outcomes occurred in 73 (8.6%) participants. The high-BMI variability group had a higher risk for adverse kidney outcomes compared to the low-variability group. High variabilities in triglyceride, fasting blood glucose, and systolic blood pressure were also associated with adverse kidney outcomes. Furthermore, high variability in metabolic syndrome-related composite indices, such as the triglyceride and glucose index and metabolic variability scores, showed a higher risk for adverse kidney outcomes. In conclusion, high variability in metabolic parameters could be associated with an increased risk of adverse kidney outcome in KT patients.